HIDDEN INTERTEXTUALITY IN THE I. BRODSKY’S VERSE "AUTUMN IN NORENSKY" - TADEVOSYAN, ANAHIT (Bulletin of Yerevan University H: Russian Philology, 2021)
I. Brodsky’s poem “Autumn in Norenskaya”, traditionally perceived as a landscape sketch, not only correlates with the tradition of the theme of autumn in Russian literature, but is also directly related to Baratynsky’s poem “Autumn”, therefore the unwritten death of Poet determines the intonation of this poem. This is shown in the article by means of a detailed analysis of rhythmic and imaginative structure of the verse.
Keywords: I. Brodsky, exile to Norenskaya